Cluster-randomised trial of the impact of an obesity prevention intervention on childcare centre nutrition and physical activity environment over 2 years. Issue 11 (1st November 2022) - Natale, Ruby; Atem, Folefac D; Lebron, Cynthia; Mathew, M Sunil; Weerakoon, Sitara M; Martinez, Catherina Chang; Shelnutt, Karla P; Spector, Rachel; Messiah, Sarah E
Abstract: Objective: The prevalence of obesity among pre-school-aged children in the USA remains unacceptably high. Here, we examine the impact of Healthy Caregivers-Healthy Children (HC2) Phase 2, a childcare centre (CCC)-based obesity prevention intervention on changes in the CCC nutrition and physical activity environment over 2 school years. Design: This was a cluster-randomised trial with twelve CCC receiving the HC2 intervention arm and twelve in the control arm. The primary outcome was change in the Environment and Policy Assessment and Observation (EPAO) tool over 2 school years (Fall 2015, Spring 2016 and Spring 2017). Changes in EPAO physical activity and nutrition score were analysed via a: (1) random effects mixed models and (2) mixed models to determine the effect of HC2 v. control. Setting: The study was conducted in twenty-four CCC serving low-income, ethnically diverse families in Miami-Dade County. Participants: Intervention CCC received (1) teachers/parents/children curriculum, (2) snack, beverage, physical activity, and screen time policies, and (3) menu modifications. Results: Two-year EPAO nutrition score changes in intervention CCC were almost twice that of control CCC. The EPAO physical activity environment scores only slightly improved in intervention CCC v. control CCC. Intervention CCC showed higher combined EPAO physical activity and nutrition scores compared to control CCC over the 2-year study period ( β = 0·09, P = 0·05). Conclusions: Obesity prevention programmes can have a positive impact on the CCC nutrition environment and can promote healthy weight in early childhood. CCC may need consistent support to improve the physical activity environment to ensure the policies remain intact.